Macrophage Activation Markers, CD163 and CD206, in Acute-on-Chronic Liver Failure - Marlene Christina Nielsen (Cells, 2020)
Macrophages facilitate essential homeostatic functions e.g., endocytosis, phagocytosis, and signaling during inflammation, and express a variety of scavenger receptors including CD163 and CD206, which are upregulated in response to inflammation. In healthy individuals, soluble forms of CD163 and CD206 are constitutively shed from macrophages, however, during inflammation pathogen- and damage-associated stimuli induce this shedding. Activation of resident liver macrophages viz. Kupffer cells is part of the inflammatory cascade occurring in acute and chronic liver diseases. We here review the existing literature on sCD163 and sCD206 function and shedding, and potential as biomarkers in acute and chronic liver diseases with a particular focus on Acute-on-Chronic Liver Failure (ACLF). In multiple studies sCD163 and sCD206 are elevated in relation to liver disease severity and established as reliable predictors of morbidity and mortality. However, differences in expression- and shedding-stimuli for CD163 and CD206 may explain dissimilarities in prognostic utility in patients with acute decompensation of cirrhosis and ACLF.